Relationship (A)Symmetries and Violence: Comparing Intimates and NonPartners. (May 2018) - Griffiths, Elizabeth; Yule, Carolyn; Gartner, Rosemary
Violence between social equals differs in character from violence between persons in asymmetrical relationships. Specifically, issues of contention motivating violence vary by the relative status of opponents, such that violence over symbolic issues is more common between symmetrical than asymmetrical opponents. Recent studies have substantiated these predictions in nonpartner relationships. Using data from interviews of incarcerated women, this study explores how intimate partner violence compares with violence between nonpartner opponents. We find that intimate partner violence is more likely to involve symbolic issues compared with violence between all kinds of nonpartner opponents. Consequently, intimate partnerships might be viewed as hypersymmetrical.